Prevalence of delayed puberty and low bone density in patients with epidermolysis bullosa: Insight from a large single center's experience. Issue 1 (25th September 2022) - Wasserman, Halley; Dumenigo, Andrea; Hornung, Lindsey; Augsburger, Bret; Marathe, Kalyani; Lucky, Anne W.
Abstract: Background: Epidermolysis bullosa (EB) is a group of rare genetic skin conditions that result in skin fragility. EB can be quite severe with chronic inflammation and malnutrition impairing growth and pubertal development. These factors have potential consequences for skeletal health. We aimed to determine the prevalence of delayed puberty and low bone mineral density (BMD) for age in children and young adults with EB. Methods: Electronic medical records (EMR) of patients with confirmed EB <30 years of age at time of initial encounter at Cincinnati Children's Hospital Medical Center between January 1, 2010 and September 30, 2020 were reviewed. Natural language processing software was used to categorize pubertal status of patients with EB as early, normal or delayed. BMD was measured by dual energy x‐ray absorptiometry and categorized as low if height adjusted Z‐score was <−2.0 using age, sex and race specific reference ranges. Results: 29% of individuals with EB had low BMD with most cases occurring prior to 10 years of age. Of patients who reached adolescence, 23% failed to develop any signs of puberty in the normal range (before age 13 in females or 14 in males) and BMD Z‐scores further declined in these individuals. Conclusion: Delayed puberty is an under‐recognized comorbidity of individuals with EB, especially in those with recessive dystrophic EB, and can have a significant impact on BMD.